Independent review of aid effectiveness - Holloway, Sandy, chair (Commonwealth of Australia CanberraAU, 2011)
Presents an independent review of the Australian aid programme. Includes analysis, findings and recommendations on concepts of aid and development; contemporary international thinking on what makes aid effective; the aid programme as it currently stands and its effectiveness; political, economic and social trends likely to shape aid and development to 2015 and beyond; vision and objectives of the future programme; geographical and sectoral priorities for the programme; partnerships and delivery of the programme; aid allocations - the shape of the future programme; governance, leadership and management; managing risk; measuring success; enhancing transparency, scrutiny and community engagement and; the steps and hurdles for moving to an effective programme in 2015-16 and beyond.